Overview of women and political participation in Nigeria (2015–2022) - Oluwatoyin Ojo (Goodwood Publishing, 2022)
Purpose: The purpose of this research is to analyze the level of women’s political participation in Nigeria. The role of women in the political affairs of developing nation leaves much to be desired, lesser roles given to women in public policy-making has not allowed for the effective galvanization of their efforts into the legislative and executive branches of government. Research methodology: This article adopts primary data through questionnaires and observation and secondary data through consultation with several textbooks, magazines, journals, and other publications. Twenty-five 25 copies of questionnaires were administered and dully returned through the adoption of simple random sampling. Results: It was observed that the level of women’s political participation is low and women don’t have equal chances of winning elections in Nigeria due to some factors like culture, religion, historical–structural, and even economic or financial factors. Limitations: Some of the major limitations to the research work are time restrictions, access to adequate kinds of literature, documents, and data that can help the researcher. Contributions: The research can be instrumental to the growth and improve the level of women’s political participation because women do not get the needed encouragement in the political arena.